Hydrocarbon Pollution Remediation Project and Environmental Remediation in Ogoni Land, Nigeria - Barikorkaka Serekara (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
The study examined the impact of the Hydrocarbon Pollution Remediation Project (HYPREP) on the environmental remediation of Ogoniland, focusing on water quality restoration, mangrove and ecosystem rehabilitation, and socio-economic recovery. The study was anchored on the Environmental Justice Theory, which emphasises equity, community participation, and livelihood restoration in addressing environmental challenges. The study adopted the qualitative research design, while the purposive and snowball sampling techniques were utilised to choose participants from selected Ogoni communities, HYPREP officials, and relevant stakeholders. Data were collected using in-depth designed interviews, focus group discussions, and document analysis, and analyzed using thematic analysis. Findings of the study revealed that HYPREP has made significant progress in the provision of potable water schemes and shoreline remediation, leading to observable improvements in some communities. However, access to clean water remains uneven, ecosystem restoration is incomplete, and socio-economic programmes limited in reach. The study concluded that while HYPREP has initiated significant remediation efforts, problems relating to sustainability, inclusiveness, and implementation persist. The study recommends expansion of water projects, strengthened ecosystem monitoring, and improved livelihood support mechanisms. The study suggests further, future research on long-term health outcomes, community participation, and comparative studies of remediation efforts in another oil-producing domain.